Climate+ for Bicol Region, Philippines: IPSR Innovation Package and Scaling Readiness Report - Castillo, Rowena; Baradas, Airene Claire; Balanza, Jane Girly; Laborte, Alice; Hellin, Jon (International Rice Research Institute, 2025)
The report presents the results of an Innovation Package and Scaling Readiness workshop aimed at designing an innovation package and identify opportunities and bottlenecks for achieving the following scaling ambition: By 2024, ClimBeR and partners will work together with the DA, local government units and input providers to catalyze use and uptake of the Climate+ by 5,000 farmers (30% women) in Bicol region contributing to the adoption of bundled agro-climatic farm-level advisories and increased rice production by 10%. The workshop was held on January 23, 2024 in Legazpi, Albay and was attended by 12 female and 17 male experts.